2016
DOI: 10.5761/atcs.cr.15-00367
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Fluorescence Navigation Thoracoscopic Metastasectomy for Pulmonary Metastasis of Hepatocellular Carcinoma

Abstract: Indocyanine green can selectively accumulate in primary hepatocellular carcinoma (HCC) and extrahepatic metastases. We report a patient who underwent resection of pulmonary metastasis of HCC using a thoracoscopic near-infrared imaging system and fluorescent navigation surgery. A 66-year-old man with suspicion of pulmonary metastasis of HCC was referred to our hospital. Indocyanine green was injected intravenously at a dose of 0.5 mg/kg body weight, 20 h before thoracoscopic surgery. An endoscopic indocyanine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Recent reports have demonstrated that ICG can selectively accumulate not only in primary HCC but also extrahepatic metastases [ 2 5 ]. ICG is selectively accumulated by the hepatocytes and excreted in the bile via an active transport system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have demonstrated that ICG can selectively accumulate not only in primary HCC but also extrahepatic metastases [ 2 5 ]. ICG is selectively accumulated by the hepatocytes and excreted in the bile via an active transport system.…”
Section: Discussionmentioning
confidence: 99%
“…Selective uptake and retention of ICG by hepatocellular carcinoma (HCC) tumors have recently been revealed, and ICG fluorescence imaging has begun to be applied as an extremely sensitive intraoperative tool for detecting foci of HCC [ 2 , 3 ]. Recent reports have demonstrated that ICG can selectively accumulate in primary HCC and extrahepatic metastases of HCC; additionally, ICG fluorescence imaging presented clear boundaries between tumors and normal tissue [ 2 5 ]. Here, we report, to the best of our knowledge, the first case of laparoscopic resection of peritoneal metastasis using ICG fluorescence imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Since fluorescence microscopy imaging can provide cellular resolution with several millimeters of penetration, it is a particularly attractive approach to detect tumor boundaries and tumor residuals. There are many nanoparticles such as quantum dots and nanoparticle conjugated or encapsulated fluorescence dye developed for tumor detection. However, many existing molecular imaging probes nonspecifically accumulate within the healthy organs of the mononuclear phagocytic system (MPS), such as liver or spleen, which could compete with the tumor for the probes. , Small molecules such as indocyanine green (ICG) were also used for detection of primary and metastatic HCC. However, ICG also could accumulate in noncancerous tissues in the liver, , which can compromise the STBR and result in false positives. In recent years, targeted fluorochromes such as folate modified FITC have been used in human ovarian cancer patients, and shown promising results; , however, similar results have not yet been reported for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Indocyanine green laser angiography has been proven to be an effective and reliable method to use in the preoperative, intraoperative and postoperative evaluation of tissue perfusion . It has been used widely in ophthalmology surgery, urosurgery, tumour surgery, neurosurgery and reconstruction surgery, among others . With the assistance of this device, we are able to locate the major perforators of the superior gluteal artery precisely and design a flap with adequate vascularity and perfusion.…”
Section: Discussionmentioning
confidence: 99%